1-Oxo-3, 4-dihydroisoquinoline-4-carboxamides as novel druglike inhibitors of poly(ADP-ribose) polymerase (PARP) with favourable ADME characteristics. (1st January 2021) - Safrygin, Alexander; Zhmurov, Petr; Dar'in, Dmitry; Silonov, Sergey; Kasatkina, Mariia; Zonis, Yulia; Gureev, Maxim; Krasavin, Mikhail
Abstract: A novel 3, 4-dihydroisoquinol-1-one-4-carboxamide scaffold was designed as the basis for the development of novel inhibitors of poly(ADP-ribose) polymerase (PARP). Synthesis of 3, 4-dihydroisoquinol-1-one-4-carboxylic acids was achieved using the previously developed protocol based on the modified Castagnoli-Cushman reaction of homophthalic anhydrides and 1, 3, 5-triazinanes as formaldimine synthetic equivalents. Employment of 2, 4-dimethoxy groups on the nitrogen atom of the latter allowed preparation of 2, 3-unsubatituted 3, 4-dihydroquinolone core building blocks. Iterative synthesis and in vitro biological testing of the amides resulting from the amidation of these carboxylic acids allowed not only drawing important structure-activity generalisations (corroborated by in silico docking simulation) but also the identification of the lead compound, 4-([1, 4'-bipiperidine]-1'-carbonyl)-7-fluoro-3, 4-dihydroisoquinolin-1(2 H )-one, as the candidate for further preclinical development. The lead compound as well as its des-fluoro analog were compared to the approved PARP1 inhibitor, anticancer drug Olaparib, in terms of their molecular characteristics defining druglikeness as well as experimentally determined ADME parameters. The newly developed series demonstrated clear advantages over Olaparib in terms of molecular weight, hydrophilicity, human liver microsomal and plasma stability as well as plasma protein binding. Further preclinical investigation of the lead compound is highly warranted.